Chloroplast Iron Transport Proteins – Function and Impact on Plant Physiology - López-Millán, Ana F.; Duy, Daniela; Philippar, Katrin (Frontiers in Plant Science, 2016)
Chloroplasts originated about three billion years ago by endosymbiosis of an ancestor of today’s cyanobacteria with a mitochondria-containing host cell. During evolution chloroplasts of higher plants established as the site for photosynthesis and thus became the basis for all life dependent on oxygen and carbohydrate supply. To fulfill this task, plastid organelles are loaded with the transition metals iron, copper, and manganese, which due to their redox capacity are essential for photosynthetic electron transport. In consequence, chloroplasts for example represent the iron-richest system in plant cells. However, improvement of oxygenic photosynthesis in turn required adaptation of metal transport and homeostasis since metal-catalyzed generation of reactive oxygen species (ROS) causes oxidative damage. This is most acute in chloroplasts, where radicals and transition metals are side by side and ROS-production is a usual feature of photosynthetic electron transport. Thus, on the one hand when bound by proteins, chloroplast-intrinsic metals are a prerequisite for photoautotrophic life, but on the other hand become toxic when present in their highly reactive, radical generating, free ionic forms. In consequence, transport, storage and cofactor-assembly of metal ions in plastids have to be tightly controlled and are crucial throughout plant growth and development. In the recent years, proteins for iron transport have been isolated from chloroplast envelope membranes. Here, we discuss their putative functions and impact on cellular metal homeostasis as well as photosynthetic performance and plant metabolism. We further consider the potential of proteomic analyses to identify new players in the field.